Linguistic politeness in villagers’ interpretation (a study based on spoken texts from the Lublin region) - Pelcowa, Halina (Papers in Linguistics, 2021)
The article discusses the language picture of rural politeness as seen through the prism of sociolinguistic and cultural-dialectological research. At present, the model of politeness which has functioned in the rural context and which is based on traditional values, such as kindness, modesty, honesty, readiness to help, gratitude and respect for human dignity, appears to be a matter of the past rather than the present. The model is reflected in the use of expressions such as: bądźcie z Bogiem ‘Go with God, God bless’, Boże dopomóc, Boże dopomóż do roboty, Boże dopomóż, Boże pomóc, Bóg wam pomóż ‘Lord help me’, niech będzie pochwalony Jezus Chrystus, niech będzie pochwalony ‘Praise be to God, Praise the Lord’, szczęść Boże ‘God bless’, z Bogiem, zostańcie z Bogiem, ‘May God be with you’ (lit. ‘Stay with God’), do widzenia ‘good bye’, dzień dobry ‘good morning’, in the majestic plural wy ‘you’ form with a polite -cie suffix employed when addressing older villagers, in the pronouns on ‘he’, ona ‘she’ used with reference to strangers, and in the imperative forms expressing permission and invitation. When young people are addressed, villagers use their names or the polite ty ‘you’-sg. form; however, when strangers are addressed, then the words pan ‘sir’, pani ‘madam’ are used. Yet more recently forms “alien” to the traditional rural culture are heard more often as well. This change has an autonomous character; it is a result of the customs-, civilization- and globalization-related processes as well as the generational change.